Pengaruh Media Flash Card Dalam Mengatasi Kesulitan Membaca Siswa Kelas I Sekolah Dasar - Hemi Wulandari; Sahkholid Nasution; Muhammad Syaifullah (Insan Zenius Ilmiah, 2025)
This study aims to determine the effect of flash card media in overcoming reading difficulties of grade I elementary school students. This research is a quantitative research with experimental research type with One Group Pretest-Posttest Design (single group pretest-final test). The population in this study amounted to 81 people with a total sample size of 27 people. Determination of the research sample using Purposive Sampling technique. Based on the data obtained from the pretest results of the influence of flash card media in overcoming reading difficulties of elementary school students and frequency distribution data in the appendix can be described as follows: the average value of students is 64.40; Variance = 20.59; Standard Deviation (SD) = 4.54; maximum value = 73; minimum value = 55, with a range of values (Range) = 18. While the data obtained from the posttest results of the influence of flash card media in overcoming the reading difficulties of elementary school students can be described as follows: the average value of students is 81.57; Variance = 24.63; Standard Deviation (SD) = 5.12; maximum value = 80; minimum value = 62, with a range of values (Range) = 18. Independent Sample t-test test in overcoming reading difficulties of grade I elementary school students is known to be a value of 2.973 and 2.05 so that Thitung> Ttable. Based on this data, it can be concluded that H0 is rejected and Ha is accepted so that it can be concluded that there is an effect of flash card media in overcoming reading difficulties.